Comparative Evaluation of Cyclooxygenase Inhibition Profiles Across Various NSAID Forms and Doses: Implications for Efficacy and Adverse Effects - Kenshu Shirakawa; Masafumi Takeno; Hidekazu Kuma; Takaaki Terahara; Shigeki Yamaguchi (Pain and Therapy)
Abstract Introduction Nonsteroidal anti-inflammatory drugs (NSAIDs) are commonly used for pain disorders and exert pharmacological effects by inhibiting cyclooxygenase (COX). Although previous studies have evaluated the COX inhibitory activity and selectivity of NSAIDs, none has compared COX inhibitory concentrations with the plasma concentrations of clinical doses or investigated the efficacy and adverse effects of different dosage forms. Therefore, in this study we evaluated the COX inhibitory activities and inhibition rates of clinical doses of the various NSAID formulations, especially diclofenac sodium. Methods Human blood and the drug (diclofenac sodium, celecoxib, ibuprofen, flurbiprofen, or etodolac) were mixed and incubated, and the supernatant was collected and quantified the COX inhibitory activity of each drug by ELISA. Logistic regression analyses were used to calculate the inhibition rates at maximum plasma drug concentration (C max) of clinical doses of marketed formulations. For diclofenac sodium, we also calculated the concentrations at which COX inhibition rates were 50% and 80% (IC50 and IC80). Results COX-2 inhibition rate at C max of clinical doses exceeded 50% except celecoxib 100 mg. For diclofenac sodium, the C max at the clinical doses of the oral and suppository formulations showed almost complete inhibition of COX-2 and an inhibition rate exceeding IC80 for COX-1. The C max at repeated doses of the transdermal formulation showed an inhibition rate above IC80 for COX-2 but below IC80 for COX-1. Discussion This result explains why gastrointestinal disorders frequently occur with oral and suppository formulations of diclofenac sodium despite its relatively high COX-2 selectivity. Although the plasma drug concentration of the transdermal formulation is lower than oral and suppository formulations, it has an inhibition rate above IC50 for COX-2, which is required for analgesic efficacy, and has a lower COX-1 inhibition rate than these formulations. Conclusion The findings explain why the transdermal formulation exerts an analgesic effect despite having a lower C max than other diclofenac sodium formulations.